Complex System Analysis of Blumeria graminis f.sp. tritici Isolates Collected in Central Hebei Province, China - Qingping Zhou; Lingli Li; Long Wang (Discrete Dynamics in Nature and Society)
Wheat powdery mildew (WPM), caused by Blumeria graminis f.sp. tritici, is a significant disease of wheat throughout the world and has resulted in substantial yield and economic losses in wheat production. It is particularly important to understand the population distribution and genetic resistance of B. graminis f.sp. tritici. In 2019, the cumulative incidence of wheat powdery mildew in China was nearly 8.7 million hm2, which seriously affected the safe production of wheat in China. However, the proportion of disease-resistant wheat varieties in actual production was relatively low, and effective disease-resistant genes were lacking. As one of the main wheat-producing provinces in China, it is of great significance for normal wheat production to understand powdery mildew resistance in Hebei province. In this study, using wheat seedling culture in vitro, the physiological races of wheat powdery mildew in central Hebei province were identified, and the population toxicity frequency was analyzed. The results were as follows: (1) 36 strains were purified and 20 physiological races were identified. Among them, the dominant race is 015, and the distribution frequency is 16.7%. Race 077 is the second dominant race. (2) The frequency of virulence genes VEra, V8, V1, V3c, and V3f in population toxicity frequency analysis was more than 70%, while the frequency of virulence genes V2, MID, V20, V21, V4b, and V4 was less than 16.7%, and 46% of virulence genes of powdery mildew were higher than 40%. It shows that the virulence gene frequency of powdery mildew in Hebei province is high, and the varieties containing Pm2 + MID, Pm20, Pm21, Pm1b, Pm1, and other disease resistance genes have a certain value inbreeding.